Next‐generation phenotyping contributing to the identification of a 4.7 kb deletion in KANSL1 causing Koolen‐de Vries syndrome. Issue 11 (2nd October 2022) - Brand, Fabian; Vijayananth, Aswinkumar; Hsieh, Tzung‐Chien; Schmidt, Axel; Peters, Sophia; Mangold, Elisabeth; Cremer, Kirsten; Bender, Tim; Sivalingam, Sugirthan; Hundertmark, Hela; Knaus, Alexej; Engels, Hartmut; et al.
Abstract: Next‐generation phenotyping (NGP) is an application of advanced methods of computer vision on medical imaging data such as portrait photos of individuals with rare disorders. NGP on portraits results in gestalt scores that can be used for the selection of appropriate genetic tests, and for the interpretation of the molecular data. Here, we report on an exceptional case of a young girl that was presented at the age of 8 and 15 and enrolled in NGP diagnostics on the latter occasion. The girl had clinical features associated with Koolen‐de Vries syndrome (KdVS) and a suggestive facial gestalt. However, chromosomal microarray (CMA), Sanger sequencing, multiplex ligation‐dependent probe analysis (MLPA), and trio exome sequencing remained inconclusive. Based on the highly indicative gestalt score for KdVS, the decision was made to perform genome sequencing to also evaluate noncoding variants. This analysis revealed a 4.7 kb de novo deletion partially affecting intron 6 and exon 7 of the KANSL1 gene. This is the smallest reported structural variant to date for this phenotype. The case illustrates how NGP can be integrated into the iterative diagnostic process of test selection and interpretation of sequencing results.